(untitled) (The Journal of DMC, 2026)
This research paper sheds light on the objectification and fate of the female protagonist, Tess in Thomas Hardy’s Tess of the d’Urbervilles from the perspective of women’s performativity and existence. How patriarchy strongly supports Tess’s adversity is the major concern of this article. The poor fate of the protagonist blesses her to live with full of miseries. She is not fortunate as a daughter, a mother, a lover, and a wife. Firstly, her objectification starts from her own mother; secondly she is destitute and her fortune never stands for her. Since her early age to adulthood, she suffers extremely and eventually condemns to death despite her naivety. By the help of feministic theories of objectification, fatalistic conspiracies and patriarchal propagandas, this article tries to justify how the innocent women suffered during Victorian period. Not only this, it also attracts the attention for the change of the social gaze to guileless women because they are not the objects to be consumed. Tess suffers on the hands of her father, master, and husband. She is merely a marionette whose death fate doesn’t even deny.